A review of polyurethane as an alternative to asphalt binder for more sustainable roads: Performance, environment, and economy - Lei Xu; Tong Lu; Zhongbo Chen; Hangtian Ni; Daquan Sun; Yufeng Tian (Journal of Traffic and Transportation Engineering (English ed. Online))
Polyurethane (PU) as an alternative for petroleum asphalt binder in pavement engineering can not only prolong the service life of the pavement, but also enable the pavement to perform multiple functions such as drainage, noise reduction, snow melting, and ice melting, and flame retardancy, providing with economic, social and environmental benefits. PU is a kind of ''wear-resistant rubber'' with high strength and good wear resistance obtained by pre-polymerization of isocyanate and polyol. In this review, the design and preparation of PU and aggregates, i.e., PU mixture, were summarized, followed by the discussion of the strength, stiffness and durability of PU mixture. Numerous creative concepts of structure and mixture design of PU pavements were summarized, and PU dosage, the curing time, temperature, and compaction times were clarified in detail. Particularly, some successful applications including poroelastic road surface (PERS), PU porous mixture (PPM), PU rubber particle mixture (PRPM), and permeable PU stabilized recycled aggregate (PPSRA) were discussed. Special attention was given to the economic and environmental benefits of PU pavement. Overall, the PU pavement can achieve the much-needed functions of modern urban roads or highways, and prolong the service life of the pavement. However, more researches are needed to explore the design methods of PU mixture and improved its road performance. In addition, reducing the price of PU to reduce the construction cost of PU mixture was also a problem that needed to be solved.